ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI TERAPI MENGUNYAH PERMEN KARET RENDAH GULA TERHADAP PENURUNAN INTERDHIALITIC WEIGHT GAIN PASIEN YANG MENJALANI HEMODIALISA - Fijri Reski Nendareswari (2022)
Interdialytic Weight Gain, abbreviated as IDWG, is an evaluation that is always carried out by hemodialysis nurses before and after hemodialysis. This is useful for providing information on how much of the weight gain is due to accumulation of fluid in the body from the dry weight of patients who routinely undergo hemodialysis. Because if IDWG reaches intolerable levels, the patient will continue to experience complications even after hemodialysis. For that reason, IDWG management is very necessary. Meanwhile, to stabilize IDWG within reasonable limits, routine hemodialysis patients are required to limit the amount of daily fluids and control the factors behind excessive fluid consumption, one of which is thirst. Therefore, the therapy of chewing mint-flavored low-sugar gum was carried out on patients at Bhayangkara Tk. I R Said Sukanto Hospital Jakarta to reduce their IDWG which was too volatile. After implementation, the patient's IDWG managed to go down. Thus, low-sugar chewing gum therapy can be used as an alternative therapy to stabilize and reduce IDWG in hemodialysis patients.Keyword : EBN, Chewing Sugar-Free Gum, IDWG, Hemodialysis